An Analysis of Turn-Taking Strategies used in EFL Classroom Interaction at Universitas Muslim Maros - Nurul Ainul; Haryanto; Fatimah Hidayahni Amin (International Journal of Business English and Communication, 2024)
The main aim of this research is to identify turn-taking strategies in students' classroom interactions, describe dominant strategies, and the impact of turn- taking strategies. This research uses qualitative descriptive research. Maros Muslim University English Department students were chosen as research subjects. Data was collected through video recordings and structured interviews. The results of this research show that: (1) The dominant turn taking in students of EFL at the English Department is holding the turn by conversation between lecturer and students. There are filled pauses and verbal fillers, Silent pauses, Lexical repetition and New start. (2) Turn taking occurs in students of EFL at English Department at Maros Muslim University. Analyzing lecturers and students in conversation to describe turn-taking patterns during the teaching and learning process in debate classes they are: Taking the turn strategy; holding the turn, and yielding the turn. In other words, filled pauses, verbal fillers, lexical pauses, silent pauses. Therefore, the yielding turn is the turn to the listener. Speakers can use prompting, appealing, and giving up strategies when giving their turn. (3). The impacts of turn taking strategy are; To smooth communication, the use of Indonesian language, challenges, lecturer's explanation, lecturer and student’s interaction